Modeling and prediction of modulus of elasticity of laminated veneer lumber based on laminated plate theory. (30th January 2019) - Wei, Peixing; Wang, Brad Jianhe; Wan, Xiaojun; Chen, Xiaohan
Highlights: The stiffness of laminated veneer lumber can be theoretically predicted based on laminated plate theory. The contribution of glue to the resinated veneer mainly depended on the glue spread and veneer thickness. The tensile modulus and bending modulus of LVL can be considered to be equal for engineering applications. Abstract: To better guide the manufacturing and application of laminated veneer lumber (LVL), a theoretical model to describe the formation of the modulus of elasticity for LVL based on the laminated plate theory is described in this work. An experiment was designed to validate the model. The results showed that the theoretical prediction agreed with the measured value. The contribution of glue to the resinated veneer mainly depended on the glue solid spread (GS) and veneer thickness, namely, for a GS of 50 g/m 2, the glue effect can be ignored when the veneer thickness was more than 1.2 mm. However, for a GS of 90 g/m 2, the veneer thickness must be more than 2.1 mm to ignore the glue effect. From the standpoint of engineering applications, the tensile and bending moduli of LVL can be considered as equal.